Influencing Factors Mother's Participation In Mother's Class Pregnant At Padang Pandir Health Center Padang City In 2023 - Diyana, Mela; Nadilla, Nadilla (Alifah Health Science Symposium Proceeding, 2023)
The high maternal mortality rate (MMR) is a critical indicator of the health status of women, the Ministry of Health said the number of maternal deaths in Indonesia in 2012 reached 359 / 100,000 live births, this figure can be pressed by carrying out this research class aims to determine the factors that influence the participation of pregnant women in the class of pregnant women. This research is an analytical research using cross sectional study design. In this study each independent variable (Knowledge, support of husband and the role of health officer) dependent variable (maternal participation in pregnant mother's class) measured at the same time. Held in February at Pegambiran Puskesmas Padang City 2018. The The result of chi square test shows that there is a significant correlation between mother's knowledge with mother participation ρ = 0,020 with OR 2,6, there is no relationship between husband support with mother participation ρ = 0,114 with OR 0,3, and there is relation between health worker role with maternal participation with ρ = 0.020 with OR 5.0. It was concluded that the higher the knowledge, and the participation of the health worker the higher the participation of pregnant mother in pregnant mother class, so the maternal mortality rate can be suppressed, the researcher suggest that pregnant mother is more active in joining pregnant mother class, because the quality of the child is determined by the mother and family attention starting from within the womb.